The next public administration : debates & dilemmas - Peters, B. Guy; Pierre, Jon (Los Angeles : SAGE, 2018)
Critically reviewing the modernization of public management reform, this book explores the past, present and future of public administration. It reasserts public administration as an integral component of democratic governance and fostering a state-citizen relationship. Wide-ranging in scope, The Next Public Administration: extends basic public administration to consider issues associated with management, governance and democracy; covers core public administration concepts and their evolution through time; draws on an international spread of examples, bringing theoretical discussions to life; includes lists of further reading--back cover.
Public administration in democratic governance -- Management and administration -- Bureaucrats versus service providers: personnel in the public sector -- Neutrality versus responsiveness -- Fragmentation versus strategy -- Simplicity versus complexity: programs and implementation -- Rationality versus routine: how do public organizations make decisions? -- Autonomy versus integration -- Rationality versus incrementalism: funding public organizations -- Authority versus democracy -- Conclusions: the new public administration.
Includes bibliographical references (pages [155]-173) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Public administration; Electronic books